Hubungan Lama Menstruasi, Gaya Hidup, dan Pola Makan dengan Kejadian Anemia pada Remaja Putri di SMK Negeri 1 Lempuing Jaya Kabupaten Ogan Komering Ilir Tahun 2021 - Arika Marlena; Fika Minata; Satra Yunola (Universitas Batanghari Jambi, 2023)
Adolescence is a transitional period characterized by physical, emotional and psychic changes. Adolescence, namely the period between 10-19 years, is a period of maturation of the human reproductive organs which is often called puberty, in puberty there are problems that are often faced by adolescents during menstruation. According to the World Health Organization (WHO) 2018 women aged 15–49 years who suffer from anemia in six countries namely Africa, America, Asia, Europe, Eastern Mediterranean, and the Western Pacific region amounted to 409 – 595 million people. The prevalence in Asia, anemia in women aged 15–45 years reaches 191 million people and Indonesia ranks 8th out of 11 countries in Asia after Sri Lanka with a prevalence of anemia of 7.5 million people at the age of 10–19 years. This study aims to find out the relationship between menstruation, lifestyle, and diet with the incidence of anemia in young women at SMK Negeri 1 Lempuing Jaya, Ogan Komering Ilir Regency in 2021. The method in this study used an analytical survey with a cross-secsional design approach so that the total sample was 81 respondents. Data collection is carried out with a questionnaire. The data were analyzed by the Chi-square test formula. Univariate analysis was obtained by students who experienced anemia as many as 35 respondents (43.2%). Normal mentruation duration 50 respondents (61.7%), unhealthy lifestyle 50 respondents (61.7%), irregular diet 44 resonden (54.3%). From the results of the Chi-square static test, the p-Value = 0.005 was obtained, this shows that there is a meaningful relationship between the duration of menstruation and anemia, p-Value = 0.018 which states that there is a lifestyle relationship with anemia in young women, p value Value = 0.013 means that there is a relationship between diet and anemia in young women. The conclusion in this study is that there is a relationship between the duration of menstruation, lifestyle, diet and anemia, in young women. It is hoped that midwives will further improve services and education to young women about reproductive health in adolescents, especially the impact of anemia on young women.